MICROPROPAGATION OF BLACK TURMERIC (CURCUMA CAESIA ROXB.) THROUGH IN VITRO CULTURE OF RHIZOME BUD EXPLANTS - Muhammad Shahinozzaman; Molla Ferdous; Muhammad Faruq; Mustafa Azad; Muhammad Amin (Journal of Central European Agriculture, 2013)
In the present study, preliminary in vitro shoots propagation of Curcuma caesia Roxb. was investigated. Rhizome buds were used as explants and were cultured on Murashige and Skoog MS medium containing 6 Benzyl adenine BA alone or in combination with a Naphthalene acetic acid NAA. The results showed that the optimum shoot proliferation was obtained from MS medium containing 3.0 micro M BA + 0.5 micro M NAA. In this growth regulator combination, maximum 99.97 per cent explants produced 10.38 shoots with 4.53 cm length after 8 weeks of culture. Although spontaneous rooting was observed after 4 weeks of cultivation with all treatments using half strength MS medium containing IBA and NAA at different concentrations, high frequency of rooting 89.76 per cent was obtained in 3.0 micro M IBA Indole 3 butyric acid containing medium. The plantlets, thus developed, were hardened and successfully established in natural soil.